2019
DOI: 10.1186/s13690-019-0360-2
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence rate of undiagnosed tuberculosis in the community in Ethiopia from 2001 to 2014: systematic review and meta-analysis

Abstract: Background: In Ethiopia individual report indicated nearly 30% of incident cases of tuberculosis remained undiagnosed. Therefore, this systematic review and meta-analysis was aimed to determine the pooled prevalence rate of undiagnosed smear positive pulmonary tuberculosis (PTB) using community based studies published in Ethiopia. Methods: MEDLINE/PubMed, 'Cochrane' library, and Google scholar databases were searched, and reference list of studies on tuberculosis in Ethiopia were reviewed. We used table to pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 25 publications
3
8
0
Order By: Relevance
“…The effect of the intervention was pronounced in Gondar where the use of the TBscore as diagnostic trigger increased the number of SP PTB patients 4-fold. This is in line with findings from South Africa (Kweza et al, 2018) and Ethiopia (Arega et al, 2019) where 71% and 67% bacteriological confirmed TB patients, respectively, went undetected when seeking health care for TB related symptoms. Both Guinea-Bissau and Ethiopia have high case detection gaps which have not improved as expected in the recent years (WHO, 2019).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The effect of the intervention was pronounced in Gondar where the use of the TBscore as diagnostic trigger increased the number of SP PTB patients 4-fold. This is in line with findings from South Africa (Kweza et al, 2018) and Ethiopia (Arega et al, 2019) where 71% and 67% bacteriological confirmed TB patients, respectively, went undetected when seeking health care for TB related symptoms. Both Guinea-Bissau and Ethiopia have high case detection gaps which have not improved as expected in the recent years (WHO, 2019).…”
Section: Discussionsupporting
confidence: 91%
“…Although the well-known criterion "cough for more than two weeks" is outdated and it is recommended to be as inclusive as possible (WHO, 2011a), it still is this symptom the healthcare workers are brought up with and remember when they screen for TB. It is the most frequently used cut off for when to suspect TB (Arega et al, 2019), even though it results in missed cases (Harries and Kumar, 2018, Kweza et al, 2018.…”
Section: Discussionmentioning
confidence: 99%
“…[ 6 ] A third of TB cases have been missed in Ethiopia [ 7 ] and a couple of undiagnosed TB cases are identified in the community that hiddenly transmit the disease. [ 8 ]…”
Section: Introductionmentioning
confidence: 99%
“…This figure is slightly lower than findings from the previous Ethiopian studies, which included 11 TB cases from the Kaffa zone, 17 10 TB cases from Oromiya region hospitals, 15 and 11 TB cases from systematic and meta-analysis studies. 27 Similarly, it is lower than findings from Ghana 28 that reported 27 missed TB cases from 410 TB suspects and 95 TB cases among 543 TB suspected patients in South Africa. 29 The difference in sputum sample evaluation could be due to the fact that previous studies used GeneXpert, which has higher sensitivity to detect TB cases than sputum smear evaluation.…”
Section: Discussionmentioning
confidence: 81%